La realimentación del asesor de tesis de posgrado: una mirada del tesista - Ramos Cumpa, María Isabel (2020)
Undoubtedly, universities play a very important role in society. They lay the foundations to discover and spread new knowledge for the development of the humanity. Currently, La Superintendencia Nacional de Educación Superior Universitaria, under the statutes of the university law 30220 (2014), has arranged that research in universities be encouraged. For this reason, the completion of a thesis is required to obtain an academic degree in postgraduate studies. This decision led universities to implement their advisory programs so that students can obtain an academic degree in the shortest possible time. In this situation, we consider that the thesis meeting is very important, however, it is more interesting to focus on the content of these meetings. For this reason, this research seeks to understand the feedback from the graduate thesis advisor from the perspective of the thesis students at some universities in Lima. From the interview carried out with the thesis students, it was concluded that, despite the effort to provide effective feedback, there are still certain deficiencies and factors that have not been taken into account for this process.